Potential of Radiation Dose Reduction by Optimizing Z-Axis Coverage in Coronary Computed Tomography Angiography on a Latest-Generation 256-Slice Scanner. Issue 2 (March 2020) - von Felten, Elia; Messerli, Michael; Giannopoulos, Andreas A.; Benz, Dominik C.; Schwyzer, Moritz; Benetos, Georgios; Rampidis, Georgios; Patriki, Dimitri; Kamani, Christel H.; Gräni, Christoph; Fuchs, Tobias A.; Pazhenkottil, Aju P.; et al.
Abstract : Objective: The purpose of this study was to quantify the reduction in radiation dose achievable by using the optimal z -axis coverage in coronary computed tomography (CT) angiography (CCTA) on a latest-generation 256-slice scanner. Methods: A total of 408 scans were reviewed that were performed on a wide-range detector scanner allowing up to 16-cm z -axis coverage (adjustable in 2-cm increments). For each CCTA study, we assessed the radiation dose (ie, dose-length product and volume CT dose index) and measured the minimum z -axis coverage necessary to cover the complete cardiac anatomy. We calculated the potential radiation dose savings achievable through reduction of the z -axis coverage to the minimum necessary. Results: The majority of the CCTA scans were performed with a z -axis coverage of 16 cm (n = 285, 69.9%), followed by 14 cm (n = 121, 29.7%) and 12 cm (n = 2, 0.5%). In the group that was scanned with a collimation of 16 cm, radiation dose could have been reduced by 12.5% in 55 patients, 25% in 195 patients, and 37.5% in 33 patients when using optimal z -axis coverage for CCTA. In the group that was scanned with a collimation of 14 cm, radiation dose could have been reduced by 14.3% in 90 patients, and 28.6% in 30 patients, whereas in the group that was scanned with a collimation of 12 cm, dose could have been reduced by 16.7% in 2 patients. Conclusions: Using correct z -axis coverage in CCTA on a latest-generation 256-slice scanner yields average dose reductions of 22.0% but may be as high as 37.5%.